OPTIMALISASI KEWENANGAN KEPALA DESA DALAM MEMBENTUK PERATURAN DESA (STUDI PADA DESA TIMBANG JAYA KABUPATEN LANGKAT ) - Siregar, Azril Arianto; Faisal, Faisal (JURNAL DOKTRIN REVIEW, 2023)
The authority of the Village Head in forming Village Regulations as ordered by Law Number 6 of 2014 concerning Villages, namely carrying out village government and forming Village Regulations. This research aims to find out what legal provisions give the Village Head the authority to form Village Regulations, and what the Village Head's efforts are in optimizing the formation of Village Regulations, as well as what are the supporting and inhibiting factors for the Village Head in forming Village Regulations. This research is empirical juridical research. The results of research in the formation of Village Regulations in Timbang Jaya Village, Langkat Regency, there are obstacles in optimizing the formation of village regulations due to limited human resource capacity and minimal community involvement in the formation of Village Regulations, even though the Village Regulations that will be formed are aimed at developing Timbang Jaya Village. Then, the formation of Village Regulations is supported by the existence of facilities and infrastructure which are very supportive in the formation of Village Regulations for the sake of the formation of Village Regulations, where facilities and infrastructure support economic, social, cultural activities, as well as national unity and unity, especially as basic capital for the realization of prosperity. community in Timbang Jaya Village, Langkat Regency